Divergence of helper, cytotoxic, and regulatory T cells in the decidua from miscarriage. (27th July 2016) - Ebina, Yasuhiko; Shimada, Shigeki; Deguchi, Masashi; Maesawa, Yoko; Iijima, Norifumi; Yamada, Hideto
Abstract : Problem: The aim of this prospective study was to evaluate phenotypic differences of helper T (Th), cytotoxic T (Tc), and regulatory T (Treg) cells in the deciduae of missed miscarriage with a normal chromosome karyotype of a fetus (MN) and missed miscarriage with an abnormal chromosome karyotype of a fetus (MA). Methods of study: The decidua of 19 MN and 28 MA was obtained. Additionally, the decidua of 15 induced abortion (IA) and the endometrium of 19 non‐pregnant women (EM) were obtained. IFN‐γ +, IL‐17 +, CD25 high Foxp3 + cells in CD4 + (Th) cells, and IFN‐γ + cells in CD8 + (Tc) cells were evaluated by flow cytometry. Results: The percentages of IFN‐γ + Tc and CD4 + CD25 high Foxp3 + (Treg) cells in MN were significantly increased as compared with MA and IA. The percentage of IFN‐γ + Th in MN was increased as compared with IA. Conclusion: Activation of IFN‐γ + Tc and Treg cells in the decidua might be associated with the pathophysiology underlying MN.